Diabetic Retinopathy Screening Programme: Attendance, Barriers and Enablers amongst Young People with Diabetes Mellitus Aged 12–26 Years - Laura N. Cushley; Katie Curran; Nicola B. Quinn; Aaron Bell; Alyson Muldrew; Una M. Graham; David R. McCance; Qing Wen; Tunde Peto (International Journal of Translational Medicine, 2021)
The study aim is to investigate characteristics, barriers and enablers for attendance at the Diabetic Eye Screening Programme Northern Ireland (DESPNI) among people with diabetes aged 12–26 years. A mixed-methods approach with retrospective analysis and prospective, questionnaire-based data collection was completed. Data were analysed using ordinal logistic regression. A questionnaire collected information on barriers and enablers to attending DESPNI. Age, diabetes duration, attendance at diabetes clinic and lower HbA1c values were significantly associated with better attendance. Those aged 12–15 were more likely to attend screening than 16–26 years, odds ratio (OR) 4.01. Subjects diagnosed less than 5 years were more likely to attend than those with longer diabetes duration (OR = 2.52, p =< 0.001). Subjects who attended diabetes clinics were more likely to attend screening (OR = 1.89, p =< 0.001) and have a lower HbA1c (OR = 1.46, p =< 0.001). Questionnaires revealed major barriers to attendance which included inconvenient appointment times, lack of access and poor communication. While many subjects were aware of the impact of diabetes on the eye, many had little understanding of screening. This study provides pivotal information on potential barriers and enablers for young people attending eye screening. We suggest modest changes such as convenient appointment times, clearer communication and one-stop clinics could improve attendance.